INFLUENCE OF LUNAR CYCLE ON OESTRUS LIKE CHARACTERISTICS AND FOLLICULAR BIOMETRY IN CROSSBRED CATTLE - S. Sandhiya; S. Satheshkumar; S. Prakash; S. Raja; S. Alagar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted to document the incidence and nature of oestrus like signs and follicular biometry during the lunar and peri-lunar days in crossbred cattle. Crossbred cattle (n = 678) which were reported to be with oestrus like signs on lunar days (full moon day and new moon day) and peri-lunar days were subjected for the investigation. Only 60.6 per cent of the animals during the study period were in actual oestrus. The remaining animals (39.4%) were found to be in various reproductive statuses viz., pregnancy (17.7%), mid-cycle oestrum (6.9%) and without any oestrus characteristics (14.8 %). The diameter of the dominant follicle in cattle with oestrus signs during lunar days (10.4 ± 0.2 mm) was significantly (P < 0.05) smaller than cattle in actual oestrus during normal days (12.2 ± 0.5 mm). Exhibition of oestrous signs with smaller follicular diameter indicated the probable chances of lunar influence on the follicular dynamics, steroidogenesis and reproductive characters in cattle.